Dietary supplementation of compound probiotics to improve performance, egg quality, biochemical parameters and intestinal morphology of laying hens - Wang, Yan; Zhang, Chaosheng; Chen, Xing; Zheng, Aijuan; Liu, Guohua; Ren, Ying; Chen, Zhimin (Frontiers in Veterinary Science, 2024)
The purpose of this study was to investigate the effects of dietary supplementation of compound probiotics on the performance, egg quality, biochemical parameters and intestinal morphology of laying hens. A total of 180 healthy 200-day-old Hyline Brown laying hens with similar initial laying rate (87.5% ± 0.2%) were randomly divided into the control group and the treatment group. Each group included 6 replicates and each replicate included 15 laying hens. The control group was provided a basal diet, while the treatment group received the basal diet supplemented with compound probiotics. The experiment lasted for 52 days. The study indicated the following outcomes: (1) The laying rate (LR) and average egg weight (AEW) of laying hens in the treatment group were significantly higher than those of the control group (p < 0.05), whereas the feed-to-egg ratio (F/E) was significantly lower (p < 0.05); (2) The yolk weight (YW), egg shape index (ESI) and albumen height (AH) were significantly higher (p < 0.05), whereas the eggshell percentage (EP) was significantly lower (p < 0.05) after the dietary supplementation of compound probiotics; (3) The treatment group significantly decreased in total cholesterol (TC), triglyceride (TG), alanine aminotransferase (ALT), aspartate aminotransferase (AST), malondialdehyde (MDA), immunoglobulin A (IgA), and immunoglobulin G (IgG) levels in serum compared to the CON group (p < 0.05). Additionally, serum levels of total protein (TP), globulin (GLB), albumin (ALB), high-density lipoprotein (HDL), alkaline phosphatase (ALP), and total antioxidant capacity (T-AOC) were significantly higher in the treatment group (p < 0.05); (4) The supplementation of compound probiotics to laying hen diets led to a significant reduction in crypt depth (CD) and the ratio of villus height to crypt depth (V/C) in the jejunum compared to the CON group (p < 0.05). In conclusion, the supplementation of compound probiotics can regulate the body metabolism and improve the intestinal morphology, thus enhancing the antioxidant capacity and immune function of the body, which in turn improves the performance and egg quality of laying hens.